Fingerprint Patterns in Women with Type 2 Diabetes Mellitus: Computerized Dermatoglyphic Analysis - Pertille, Fabiane; Alberti, Adriano; Jesus, Josiane Aparecida de; Silva, Bruna Becker da; Souza, Renan; Abreu, Guilherme Rosa de; Comim, Clarissa Martinelli; Nodari Junior, Rudy José (Acta Scientiarum. Health Sciences, 2023)
Dermatoglyphics can be used as a supporting tool in the early detection of type 2 Diabetes Mellitus in women. The present study aims to investigate the fingerprints of women with type 2 diabetes mellitus through the dermatoglyphic method, and to compare them with women without the disease. It was conducted by obtaining the fingerprints of all 10 fingers of 268 women – which is known as the dermatoglyphic method –, using the Dermatoglyphic Reader®, with data processed in SPSS (IBM SPSS), version 20.0, and a significance level of p< 0.05. The researched groups are homogeneous for the age, weight and height variables. The group of women with diabetes had a higher average number of lines on the left thumb, as well as the highest total number of lines on the left hand. Moreover, they had a greater number of deltas, in addition to presenting the whorl shape on fingers 1 to 5 of the left hand, and 1 to 4 of the right hand. We concluded that women with type 2 diabetes had a mark of observation concerning their biological individuality on their fingerprints that differs from that of women without the disease.